Perbedaan Pengetahuan Pemeliharaan Kesehatan Gigi dan Keterampilan Menyikat Gigi Sebelum dan Sesudah Diberikan Penyuluhan dengan Media Video Animasi - Supariani, Ni Nyoman Dewi; Sari, Ayu Made Putri Kartika; Arini, Ni Wayan; Wirata, I Nyoman (Jurnal Kesehatan Gigi (Dental Health Journal), 2025)
The results of the Basic Health Research data (2018) in the 10-14 year age group showed that 97.58% brushed their teeth every day but 3.68% brushed their teeth at the correct time. This study aims to determine the differences in knowledge of dental and oral health maintenance and tooth brushing skills of fourth grade students of Muhammadiyah 2 Denpasar Elementary School before and after being given counseling using animated video media. This study is an analytical study using the Wilcoxon test. The number of respondents was 50 students. The results showed an increase in students' knowledge and skills. Before counseling, the largest percentage of knowledge was 28 students (56%) with sufficient criteria, after being given counseling, the largest percentage was 40 students (80%) with good criteria. The average knowledge before being given counseling was 71.80 with sufficient criteria and after being given counseling it became 83.20 with good criteria. The highest percentage of skills was 37 students (74%) with the criteria need guidance. After being given counseling, there were 34 students (68%) with very good criteria. The average skill before counseling was 50.875 criteria need guidance and after counseling was given 85.625 criteria very good. The results of the Wilcoxon test on students' knowledge and skills with a significance value of Sig (2 tailed) of 0.000 is smaller than 0.05. It can be concluded that there is a difference in knowledge of dental health maintenance and tooth brushing skills before and after counseling with animated videos.